(untitled) (Revista Rupturas, 2016)
In this paper we approach the various practices that occur within the processes of spatial construction exercised by people when they inhabit public space, as the appropriation of public space for sex between men, activity which it is muted in some social spheres, although its exercise is ancient (Sennett , 1994) and still continues to be carried out today by hundreds of people. Relevant data on frequency, displacement and types of this practice is discussed as a result of an ethnographic exercise done for the course of Recreation and Public Space, for the second half of 2014 of the Master of Landscape Design Site and the University of Costa Rica (UCR).